Using Finite Element simulation to investigate the effect of cutting edge radius on burr formation for inclined dimple milling operation - Mohd Ali Hanafiah, Shaharudin; Ahmad Razlan, Yusoff (Malaysian Tribology Society (MYTRIBOS), 2023)
In any mechanical cutting operation including micromilling, burr formation is unavoidable due to the plastically deformed materials generated from the cutting and shearing phenomenon. Compared to macro milling, the size ratio between burr and micro-milling profile is extremely large making the removal process extremely challenging. Due to the challenge, this paper presents the investigation of critical factors in burr formation such as tool cutting edge radius, Rc using the finite element (FE) approach. The first part of the investigation consists of the validation of the FE simulation results with the experimental by comparing the generated cutting force, and the second part focused on the virtual experiment on the investigation of tool cutting edge radius to the burr formation on the machined dimple profile. In the simulation of inclined dimple milling, the 3D model of solid carbide (WC) ball end mill (BEM) tool contact with the round Aluminum Alloy 6061-T6 specimen model at 45° inclination angle to form the dimple profile and the characteristic of the burr profile measured directly on the deformed specimen model. Based on the results, it was found the cutting edge radius, directly proportional to the cutting force and significantly influence the burr formation in inclined dimple milling.